Pemanfaatan Daun Lamtoro Dan Limbah Air Kelapa Dengan Penambahan Feses Sapi Untuk Pembuatan Pupuk Organik Cair - WAHYU SAPUTRA, SEPTA; , Dra. Aminah Asngad, S.Si, M.Si (2016)
Liquid organic fertilizer is a solution that contains one or more substances needed by plants soluble, which is derived from the solution of decomposition of crop residues, animal and human feces. Lamtoro leaf extract, coconut water and cow dung can be combined to produce liquid fertilizer. Nitrogen, phosphorus, potassium, calcium, and magnesium is a compound contained in lamtoro leaf extract, coconut water and cow dung. The purpose of this study to determine the content of nitrogen and phosphorus in liquid organic fertilizer leucaena leaf extract and extract of bean sprouts with the addition of cow urine. This research method completely randomized design (RAL)with two factors, a factor of 1: leaf extract concentration leucaena and coconut water 82ml: 168 ml (K1), 125 ml: 125 ml (K2), 168 ml: 82 ml (K3) and factor 2: Cow feces 75 ml (I1), 80 ml (I2), 85 ml (I3). The results showed that . Macronutrient content of highest nitrogen in treatment K3I3 is 0.22% and the lowest nitrogen content in treatment K1I1 is 0.17%. While the macronutrient content of highest phosphorus is in treatment K3I1is 0,16% and lowest phosphorus concentration in the K1I1 : 0,12%.